Cause of death analysis and temporal trends in survival after liver transplantation for transthyretin familial amyloid polyneuropathy. (2nd October 2018) - Algalarrondo, Vincent; Antonini, Teresa; Théaudin, Marie; Chemla, Denis; Benmalek, Anouar; Castaing, Denis; Cauquil, Cécile; Rouzet, François; Mika, Delphine; Duong, Eric; Dinanian, Sylvie; Eliahou, Ludivine; et al.
Abstract: Background: Hereditary transthyretin amyloidosis (ATTR) is a multisystemic disease involving mainly the peripheral nervous system and the heart. Liver transplantation (LT) is the reference treatment for ATTR neuropathy and preoperative detection of high risk patients is crucial. We aimed to document the causes of death of ATTR patients after LT, their temporal trends, and to evaluate whether the available preoperative tools that predict the risk of death after LT for hereditary ATTR amyloidosis matched with these trends. Methods: A retrospective longitudinal cohort study was performed on 215 consecutive ATTR patients who underwent LT between January 1993 and January 2011. Each patient's death cause and timing were classified. Results: Over a median follow up of 5.9 years, 84 patients died. The rate of death was higher in the first year following LT than thereafter (13.0 vs. 4.3 ± 1.8%/year; p  = .004). Cardiac events ranked as the leading cause of death (C: 38%), followed by infections (I: 24%), graft complications (G: 17%), end stage amyloidosis, stroke and others (ASO: 7% each). Deaths due to graft complications and infections (GI) occurred earlier than those due to end stage amyloidosis and stroke. Death prediction was less accurate for GI-related mortality than for other causes, which blunted the accuracy of the early-term risk prediction scores. Conclusions In ATTR amyloidosis, cardiac events were the leading cause of death after liver transplantation. Close preoperative evaluation allowed for accurate mid-term prediction of mortality, but the high rate of graft complications and infections blunted the early-term risk prediction.